2016
DOI: 10.1177/1938640016640891
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Total Ankle Arthroplasty Survival in the United States Using Multiple State Databases

Abstract: Therapeutic, Level IV: Observational study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 36 publications
2
32
1
Order By: Relevance
“…Of these readmissions, TAA-related readmissions totaled 3.5% of patients while 4.4% had a readmission that would count toward the bundle. Although LaMothe et al and Zhou et al determined that higher Charlson-Deyo comorbidity index and increased length of hospital stay were associated with 90-day readmission, neither of these factors were significantly associated with any of our study outcomes 6,7 . The current study further analyzed specific comorbidities and determined that none of the Elixhauser and Charlson-Deyo comorbidities were significantly associated with the outcomes of all-cause 90-day post-discharge readmission, TAA-related 90-day post-discharge readmission and ED visitation, or CJR-included readmissions in univariate or multivariable analysis.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Of these readmissions, TAA-related readmissions totaled 3.5% of patients while 4.4% had a readmission that would count toward the bundle. Although LaMothe et al and Zhou et al determined that higher Charlson-Deyo comorbidity index and increased length of hospital stay were associated with 90-day readmission, neither of these factors were significantly associated with any of our study outcomes 6,7 . The current study further analyzed specific comorbidities and determined that none of the Elixhauser and Charlson-Deyo comorbidities were significantly associated with the outcomes of all-cause 90-day post-discharge readmission, TAA-related 90-day post-discharge readmission and ED visitation, or CJR-included readmissions in univariate or multivariable analysis.…”
Section: Discussioncontrasting
confidence: 64%
“…Zhou et al reported a 30-day readmission rate of 2.7% that was associated with male sex, history of community-acquired pneumonia, and increased comorbidity burden 6 . Additionally, LaMothe et al reported a TAA 90-day readmission rate of 6.9% that was associated with increased length of stay following the index procedure and elevated Charlson-Deyo comorbidity index 7 . However, the specific risk factors contributing to readmission were not reported in these studies.…”
mentioning
confidence: 99%
“…21 Over the last decade, total ankle arthroplasty (TAA) has become increasingly popular as a means of alleviating the pain and functional deficits associated with arthritis of the ankle. 16…”
Section: Introductionmentioning
confidence: 99%
“…Different TAA designs: 5, 10 and 15 year survivals Table 1 summarizes the 5, 10 and 15 year survivals of different existing TAA designs . The reported 5-year survival rate in United Sytes was 90.1% [40] . Kamrad et al found that revision TAA has a 10year survival of 55%, which is lower than the 10-year survival of 74% for primary TAA published from the same registry [41] .…”
Section: Long-term Survivalmentioning
confidence: 99%
“…It has ben observed that patients with rheumatoid arthritis or who were readmitted within 90 days of TAA had significantly augmented risk of failure. Risk factors for readmission were Charlson-Deyo Score ≥ 2 and increased length of stay during TAA [40] .…”
Section: Failure Risk Factors Of Taamentioning
confidence: 99%